Pengaruh Pengetahuan Keuangan Terhadap Perilaku Keuangan Dengan Self-Efficacy Dan Sikap Keuangan Sebagai Variabel Mediasi - Mardiana, Ana; Limbok, Jeni Tiktania Laurensa; Kampo, Kunradus (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This study is an explanatory research that builds causal relationships. The purpose of this study is to investigate the effect of financial knowledge on financial behavior with self-efficacy and financial attitudes as mediating variables. The theories used are theory of planned behavior and social cognitive theory. This study uses purposive sampling method in sample selection. The sample used was students majoring in accounting class 2019-2020 Atma Jaya University Makassar. The data collection method used was through a questionnaire. The analysis technique used is path analysis and sobel testing. The results of this study indicate that financial knowledge has a positive and significant effect on financial behavior. Financial knowledge has a positive and significant effect on self-efficacy. Financial knowledge has a positive and significant effect on financial attitudes. Financial attitudes have a positive and significant effect on financial behavior. Self-efficacy has a positive and insignificant effect on financial behavior. Self-efficacy has a positive and insignificant effect in mediating the effect of financial knowledge on financial behavior. Financial attitudes have a positive and significant effect in mediating the effect of financial knowledge on financial behavior.